ANALISA DAN PERANCANGAN SISTEM INFORMASI PEMESANAN TIKET TRAVEL MELALUI SMS GATEWAY (STUDI KASUS PADA TRAVEL DANA MUKTI) (Information Technology and Telematics, 2013)
SMS Gateway application by using Short Massage Service (SMS) is a service of technology for convey the massage in shor time. The amusement of people in using SMS, which is more cheap, praetical, and there ase in all of kinds of phone, make this fitur have involve in the use of bisnis field.  This application is made using the PHP Programmed language and gammu that is used for connection PC and handphone. Handphone that used in making application is Sony Ericson W200i, which is a modem.  The fending of this reasearah is produce a reservation application program and a reminder arrival schedule of ticket in Travel Dana Mukti which basis of SMS. The application can help the passangers to know the arrival schedule and can reservation the ticket in the day and date which the passanger want to. Keywords -- SMS (Short Message Service), Gammu, SMS Gateway, SMS Reminder, SMS Autorespond.